Spatial Analysis of Heavy Metals in Soil at East and West Area of the Tigris River's In Baghdad Using GIS and Remote Sensing Techniques - Maryam Basim Musa; Sundus A. Abdullah Albakri; Maitham A. Sultan (Iraqi Journal of Physics, 2025)
Heavy metal pollution is one type of pollution that can affect soil and plants. The research uses spatial analysis techniques to evaluate soil pollution with heavy metals in the areas east and west of the Tigris River in Baghdad. Thirty five soil samples were collected from the study area and analyzed using atomic absorption spectoscopy. When comparing the concentrations of metals (cadmium, lead, nickel, iron, and copper) in the soil samples with the permissible limit, it was found that they were arranged as follows: Cd > Ni > Pb > Cu > Fe. Cd concentrations range was 3.55-5.4 ppm, Pb concentrations range 1.445-8.2 ppm, and Ni concentration 4.7-9.35 ppm. Fe was found in very small proportions compared to the permissible limit, as the concentration of Fe ranged from 43.1 ppm to 70.15 ppm. Cu concentrations in the soil of the study area ranged from 0.47 ppm to 4.86 ppm. Cd concentrations exceeded the permissible limit in the soil of the study area, and the results indicate that the area suffers from Cd pollution. The spatial analysis maps also indicated the accumulation of Cd throughout the study area, indicating the causes of pollution with this metal, such as using sewage water for irrigation and pesticides and fertilizers containing Cd. Cd is an inorganic metal, so if it accumulates in the soil, it can be absorbed by plants and accumulate in edible parts such as leaves and roots.